2008
DOI: 10.1371/journal.pone.0003520
|View full text |Cite
|
Sign up to set email alerts
|

TOR Regulates Cell Death Induced by Telomere Dysfunction in Budding Yeast

Abstract: Telomere dysfunction is known to induce growth arrest (senescence) and cell death. However, the regulation of the senescence-death process is poorly understood. Here using a yeast dysfunctional telomere model cdc13-1, which carries a temperature sensitive-mutant telomere binding protein Cdc13p, we demonstrate that inhibition of TOR (Target of Rapamycin), a central regulator of nutrient pathways for cell growth, prevents cell death, but not growth arrest, induced by inactivation of Cdc13-1p. This function of TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The arrest is accompanied by ROS formation and activation of a protease with caspase-like activity [ 16 ]. Long term arrest irreversibly blocks further proliferation, while inhibition of mTOR pathway prevents the viability loss [ 17 ]. This shows a striking similarity of arrest-induced irreversible proliferation block (death) in yeast and senescence in higher eukaryotic cells proposed earlier [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The arrest is accompanied by ROS formation and activation of a protease with caspase-like activity [ 16 ]. Long term arrest irreversibly blocks further proliferation, while inhibition of mTOR pathway prevents the viability loss [ 17 ]. This shows a striking similarity of arrest-induced irreversible proliferation block (death) in yeast and senescence in higher eukaryotic cells proposed earlier [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, as the loss of mitochondrial DNA causes major changes in the physiology of yeast cells, there could be multiple reasons for the increased viability during prolonged arrest in S-phase. Qi et al [ 16 , 17 ] suggested that the increased viability was due to suppression of mitochondrial ROS production caused by the loss of functional respiratory chain. Consistent with this, it was shown that antioxidants N-acetylcysteine and ascorbic acid prevented yeast cell death induced by telomere dysfunctioning [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S3). Dysfunctional (uncapped or short) telomeres have been shown to elicit the DNA damage response pathway, leading to accumulation of single-stranded DNA (ssDNA), activation of the DNA damage checkpoint (Dewar and Lydall, 2010;Longhese, 2008;Maringele and Lydall, 2002;Teo and Jackson, 2001;Zubko et al, 2004) and cell cycle arrest or delay (IJpma and Greider, 2003;Pang et al, 2003;Qi et al, 2008Qi et al, , 2003. Therefore, we wanted to know whether the slow growth of arv1Δ mutant was due to activation of a telomeric DNA damage checkpoint.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, our results suggest that the arv1Δ mutant activates an Exo1-and MRX (Mre11-Rad50-Xrs1)-dependent DNA damage checkpoint, and that overexpression of telomerase subunits counteracts apoptotic signals triggered by impaired sphingolipid metabolism. As dysfunctional telomeres have been shown to result in activation of the DNA damage checkpoint (Dewar and Lydall, 2010;Longhese, 2008;Maringele and Lydall, 2002;Teo and Jackson, 2001;Zubko et al, 2004), cell cycle arrest in G2/M (IJpma and Greider, 2003;Pang et al, 2003;Qi et al, 2008) and apoptotic cell death (Qi et al, 2008(Qi et al, , 2003, it is tempting to speculate that the telomeric regions in the arv1Δ mutant are not protected from DNA damage checkpoint signaling. Previous observations have shown that a reduction in the amount of complex sphingolipids caused by AbA treatment or acc1 mutation, but not lcb1-100 mutation, induced cell cycle G2/M arrest (Al-Feel et al, 2003;Endo et al, 1997;Jenkins and Hannun, 2001) and that the arv1Δ mutant exhibited a synthetic growth defect with the cdc13-1 mutant leading to uncapped telomeres (Addinall et al, 2008) are consistent with the hypothesis.…”
Section: Discussionmentioning
confidence: 99%